Ecuaciones e inecuaciones - Vilca Flores, Mary Luz (2019)
The following professional sufficiency dissertation regarding equations and inequations is aimed for students coursing the first grade of secondary school in the city of Trujillo during the present year, 2019. The main goal is to generate significative cognizance by linking mathematical knowledge to everyday situations, meaning students will be able to spot the relationship between the given data and the unknown values of equality or inequality and convert them into equations or inequations with natural numbers. The following professional sufficiency dissertation regarding equations and inequations is aimed for students coursing the first grade of secondary school in the city of Trujillo during the present year, 2019. The main goal is to generate significative cognizance by linking mathematical knowledge to everyday situations, meaning students will be able to spot the relationship between the given data and the unknown values of equality or inequality and convert them into equations or inequations with natural numbers. Mathematical, pedagogical and didactical processes have been applied in the elaboration of the learning session, with the purpose of strengthening significant learning. The strategies used were made to encourage the active and meaningful participation of all students. Our overall goal is to motivate and awaken the student’s interest for mathematics.